Provider discussion of health goals and psychosocial needs: Comparing older to younger veteran experience. (21st September 2022) - Cogan, Alison M.; Saliba, Debra; Steers, W. Neil; Frochen, Stephen; Lynch, Kimberly A.; Ganz, David A.; Washington, Donna L.
Abstract: Objective: To examine by age, the veterans' report on whether components of age‐friendly health systems were discussed during primary care visits. Data Sources and Study Setting: Veterans Affairs (VA) Survey of Healthcare Experience of Patients from October 2015 to September 2019. Study Design: Cross‐sectional survey of VA users by age group (18–44 years, 45–64 years, 65+ years; N = 1, 042, 318). We used weighted logistic regression models to evaluate disparities in whether veterans discussed with anyone in their provider's office: health goals, depression symptoms, stress, personal problems, and medications. Models were adjusted for socio‐demographic characteristics (sex, socioeconomic status, education, rurality) and comorbidity. Data Collection/Extraction Method: Surveys were administered by mail and online. Additional veteran characteristics were extracted from VA administrative data. Principal Findings: In unadjusted analyses, VA users age 18–44 had a higher (−8.2%; CI: −9.0, −7.3) and users aged 45 to 64 had lower (4.0%; CI: 3.7, 4.3) predicted, probably discussing health goals compared to age 65+. Fewer VA users age 65+ reported discussing depression symptoms, personal problems, and stress than other age groups, whereas more VA users age 65+ discussed medications. Results were unchanged after adjusting for socio‐demographics and comorbidity. Conclusions: Delivery of goal‐concordant care relies on understanding the needs of individual patients. Lower rates of discussing what matters and mood represent potential missed opportunities to deliver age‐friendly care for older veterans.